Sanitary profile of the goat and sheep flocks in the North of Minas Gerais State, Brazil - Almeida, Anna Christina de; Teixeira, Lucas Magalhães; Duarte, Eduardo Robson; Morais, Greiciele de; Silva, Bárbara Cardoso da Mata e; Geraseev, Luciana de Castro (Comunicata Scientiae, 2010)
The objective of this study was to evaluate the occurrence of infectious and contagious diseases inherds of sheep and goats in northern Minas Gerais State, Brazil. Visits were carried out to eighteenbreeders of sheep and goats, six visits in the region of Montes Claros, three in the core production ofFrancisco Sá, two in Janaúba, two in Coração de Jesus and five Ibiaí in the municipality, with fourcores in total production. The total number of animals in these properties was 2,052. Was carriedout through interviews, questionnaires to collect data on the occurrence of diseases and diarrheawas observed in young animals in 94.4% of the properties, caseous lymphadenitis in 88.9%, 33.3% inmastitis, foot pad dermatitis in 25.0%, conjunctivitis in 22.3%, contagious ecthyma in 11.1% and 5.55%in enterotoxemia. Only seven property held sporadic vaccination against clostridiosis. Practiceproper hygiene of premises and environments and handling young animals were not adopted.These figures are worrying, considering that the levels of occurrence of diseases was high. It is theneed for formation of a culture among producers that prophylactic measures should prevail on thehealing, because they represent higher costs and lower profit.